Old Age Security of Women in the Twelve EC-Countries - To What Extent are Beveridge's Two Main Principles of Universality and Guaranteed Minimum Fulfilled? - Frank Tibitanzi; Gabriele Rolf; Richard Hauser; Diether Doring (Luxembourg Income Study (LIS), 1992)
This is a comparative study of the core old-age security systems in the twelve member states of the EC applying the two main principles of the Beveridge Plan as standards of reference. The focus is on comparison of differences in benefit provision for (old age) women of these EC countries, questioning gender neutrality.
Keywords: 330